Introdução e aplicação da diluição da precisão das ambiguidades GNSS - ADOP - Monico, Jõo Francisco Galera [UNESP]; Rofatto, Vinicius Francisco [UNESP]; De Mendonça, Marco Aurélio Moraes [UNESP] (My University, 2014)
The main topic of this paper is the Ambiguity Dilution of Precision known as ADOP. Basically, ADOP is defined as a diagnostic measure for assessing the precision of the float scalar ambiguities. Among the several possibilities, the ADOP can provide help in predicting the behavior of a baseline or a network of GNSS receivers, concerning the problem of ambiguity resolution, either in real-time (instantaneous) or in the post-processing mode. The main advantage of using ADOP is possibility of the extraction of a closed analytical expression, considering various factors that affect the ambiguity resolution. Furthermore, the ADOP is related to the success rate of ambiguity resolution. The expressions here used, takes into account several factors, for example, a priori information of the measurement precision of GNSS carrier phase and pseudorange, the number of stations and satellites, the number of available frequencies and the behavior of the atmosphere (ionosphere and troposphere). Several scenarios were established so as to analyze the impact of each factor in ambiguities resolution, within the context of some stations of the São Paulo GNSS network (GNSS-SP).
Introduction and application of the GNSS Ambiguity Dilution of Precision-ADOP
Keywords: ADOP; Carrier phase ambiguity resolution; Gnss